On the distribution in Italy of the Nearctic cypress aphid Siphonatrophia cupressi (Swain 1918) (Aphididae Aphidini). (Bollettino di zoologia agraria e bachicoltura, 2024)
Further findings of the Nearctic Cypress aphid Siphonatrophia cupressi (Swain 1918) in Italy (Lombardy, Tuscany, Sicily) are reported. This species lives on some genera of Cupressaceae (Cupressus, Juniperus, Widdringtonia, Cupressocyparis) and was found for the first time in Europe (France and Italy) in 1999.
Keywords: Aphididae; Siphonatrophia cupressi; Cupressacee; Italy; Europe